I can factor everything up until i get to the last two terms that require me to multipy the square roots and there after... Thanks in advance for any help!!
(-5+sqrt(-9)) (7-sqrt(-1))
Hi tarabshort,
Here are the steps to multiply these 2 complex expressions:
$\displaystyle (-5+\sqrt{-9})(7-\sqrt{-1}=$
$\displaystyle (-5+3i)(7-i)=$
$\displaystyle -5(7-i)+3i(7-i)=$
$\displaystyle -35+5i+21i-3i^2=$
$\displaystyle -35+26i+3=$
$\displaystyle -32+26i$
Edit: I'm too slow today, Skeeter. I'm using a dial-up connection.